1995
DOI: 10.1093/jat/19.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Ethanol Determination: Comparison of Lactate and Lactate Dehydrogenase Interference in Three Enzymatic Assays

Abstract: Gas chromatography is considered to be the reference method for ethyl alcohol determination. However, enzymatic ethanol assays have been developed for use in the clinical laboratory by several commercial vendors. Essentially, these assays utilize the oxidation of ethyl alcohol to acetaldehyde with concurrent reduction of nicotinamide adenine dinucleotide (NAD) to NADH while monitoring the increase in absorbance at 340 nm. The increase in absorbance is theoretically proportional to the ethanol concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Most likely the serum ethanol levels quantified via the serum ethanol assay (Beckman UniCel DxC, Beckman Coulter Inc, Brea, CA) were falsely elevated due to interference from the patient's profoundly elevated lactate dehydrogenase (LDH) (11,108 IU/L, 19 h after presentation) and lactate levels (10.7 mmol/ L, 19 h after presentation). This interference of LDH and lactate with serum ethanol determination has been described with multiple instruments/assays, including the methodology used to measure ethanol in this case [26][27][28]. These assays are based on the conversion of ethanol to acetylaldehyde by alcohol dehydrogenase reducing NAD to NADH in the process, which is quantitated by absorbance at 340 nm due to NADH formation.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely the serum ethanol levels quantified via the serum ethanol assay (Beckman UniCel DxC, Beckman Coulter Inc, Brea, CA) were falsely elevated due to interference from the patient's profoundly elevated lactate dehydrogenase (LDH) (11,108 IU/L, 19 h after presentation) and lactate levels (10.7 mmol/ L, 19 h after presentation). This interference of LDH and lactate with serum ethanol determination has been described with multiple instruments/assays, including the methodology used to measure ethanol in this case [26][27][28]. These assays are based on the conversion of ethanol to acetylaldehyde by alcohol dehydrogenase reducing NAD to NADH in the process, which is quantitated by absorbance at 340 nm due to NADH formation.…”
Section: Discussionmentioning
confidence: 99%
“…HIV RNA was determined by a commercial NASBA assay (Organon Teknica, Bostel, The Netherlands), with a detection limit of 80 copies/mL. CD4+ T cells were determined by flow cytometry (FACScan; Becton Dickinson, Erembodegem Aslst, Belgium), and blood lactate levels were analyzed as described [19].…”
Section: Methodsmentioning
confidence: 99%
“…Although it had been suggested that lactate alone can interfere with the ADH-based assay by "cross-reaction," lactate, as noted previously (8), is not an effective substrate for ADH. It is, however, reasonable to suggest that the combination of high levels of both lactate and LDH can, in the presence of the excess NAD + in the assay, produce NADH and thereby cause a falsely elevated ethanol reading as reported by Nine et al (10), who also demonstrated the differential susceptibility of specific assays to this interference. Serum lactate increases rapidly after death, even in the early postmortem period (11).…”
Section: Resultsmentioning
confidence: 85%